Pelatihan Pengembangan Kompetensi Guru Abad 21 pada PAUD Aisyiyah Ganjar Agung Metro - Sakung, Nikki Tri; Nofiansyah, Wahyu; Fitriana, Ana; Trianto, Yohanes Adi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Changing times continue to grow, the role of the teacher has undergone significant changes. Teachers must have a variety of competencies that are able to face the challenges and demands of increasingly complex education. Teachers need to continue to learn, adapt, and develop themselves in order to provide effective and relevant education for students in the modern era. PAUD (Early Childhood Education) teachers must have specific competencies that enable them to face the challenges and demands of teaching early childhood. These competencies will help PAUD teachers to provide quality education that is relevant and supports the holistic development of early childhood in the 21st century. Based on these conditions, knowledge and skills are needed to develop pedagogical competence as a qualified PAUD educator. This training was held at Aisyiyah PAUD, Ganjar Agung District. The results of the questionnaire at the end of the training activities showed that 77.5% of the participants said the activities were useful and 77.9% said the training was interesting.